The effects of Latino Dance intervention on academic and general self-efficacy with left-behind children: An experimental study in China - Zhou, Zhenqian; Zhou, Yutao; Ferraro, Francesco Vincenzo; Hooton, Andy; Ribchester, Chris (Frontiers in Psychology, 2023)
Although there is considerable research indicating that physical exercise and dance can strengthen children's self-efficacy, and children's self-efficacy can predict students' academic achievement at a wide range of academic levels. Few studies have been conducted using Latino Dance to improve self-efficacy in Left-Behind Children (LBC), especially the two aspects of student academic self-efficacy and general self-efficacy, while the mediator role of self-esteem between student academic self-efficacy and general self-efficacy has been less explored in previous research. This study proposed to examine Latino Dance interventions to improve general self-efficacy and students’ academic self-efficacy among LBC students in rural areas to boost students’ academic performance, and research team hypothesized that general self-efficacy, students’ academic self-efficacy and self-esteem will improve following the intervention and that outcomes will have a significant positive correlation as students’ self-esteem can mediate both their academic self-efficacy and their general self-efficacy. Dates were collected form 305 LBCs’ children (160 boys and 145 girls) from 6 left-behind schools in Hunan province, China. Ralf Schwarzer's general self-efficacy scale, Morgan-Jinks Student academic Self-Efficacy Scale, and Rosenberg's self-esteem scale were administered to LBCs between September 2020 and January 2022. The results revealed that the Latino Dance intervention signiﬁcantly increased the LBC student’ academic self-efficacy and general self-efficacy, which also involved positive effect on the three sub-dimensions (talent, context, and effort) of student’ academic self-efficacy. Further, multiple linear regression analysis confirmed that self-esteem (positive esteem/self-deprecation) acted as a partial mediator between student academic self-efficacy and general self-efficacy; perceived self-esteem played a mediating role between them. This study fills a gap in the literature concerning the psychological reinforcement effect of Latino Dance on LBC groups and demonstrated that Latino Dance improved the student’ academic self-efficacy and general self-efficacy among the LBCs. Our results suggests that Latino Dance can be beneficial for LBC in school by including Latino Dance in Physical Education or Art courses and improving students' self-esteem may lead to an increase in student academic self-efficacy as well as general self-efficacy thereby improving and enhancing the learning of LBCs.